Role of exercise-induced reactive oxygen species in the modulation of heat shock protein response. (January 2014) - Fittipaldi, S.; Dimauro, I.; Mercatelli, N.; Caporossi, D.
Abstract The multiple roles that have been associated with heat shock proteins (HSPs), inside and outside cells are remarkable. HSPs have been found to play a fundamental role in multiple stress conditions and to offer protection from subsequent insults. Exercise, because of the physiological stresses associated with it, is one of the main stimuli associated with a robust increase of different HSPs in several tissues. Given the combination of physiological stresses induced by exercise, and the 'cross-talk' that occurs between signaling pathways in different tissues, it is likely that exercise induces the HSP expression through a combination of 'stressors', among which reactive oxygen species (ROS) could play a major role. Indeed, although an imbalance between ROS production and antioxidant levels results in oxidative stress, causing damage to lipids, proteins, and nucleic acids with a possible activation of the programed cell death pathway, at moderate concentrations ROS play an important role as regulatory mediators in signaling processes. Many of the ROS-mediated responses actually protect the cells against oxidative stress and re-establish redox homeostasis. The aim of this review is to provide a critical update on the role of exercise-induced ROS in the modulation of the HSP's response, focusing on experimental results from animal and human studies where the link between redox homeostasis and HSPs' expression in different tissues has been addressed.